Survival of spin state in magnetic porphyrins contacted by graphene nanoribbons - Li, Jingcheng (Sci Adv, 2018)
We report on the construction and magnetic characterization of a fully functional hybrid molecular system composed of a single magnetic porphyrin molecule bonded to graphene nanoribbons with atomically precise contacts. We use on-surface synthesis to direct the hybrid creation by combining two molecular precursors on a gold surface. High-resolution imaging with a scanning tunneling microscope finds that the porphyrin core fuses into the graphene nanoribbons through the formation of new carbon rings at chemically predefined positions. These ensure the stability of the hybrid and the extension of the conjugated character of the ribbon into the molecule. By means of inelastic tunneling spectroscopy, we prove the survival of the magnetic functionality of the contacted porphyrin. The molecular spin appears unaffected by the graphenoid electrodes, and we simply observe that the magnetic anisotropy appears modified depending on the precise structure of the contacts.